Dna damage in myocardial cells of rats with experimental alcoholic cardiomyopathy: modifyng effects of fabomotizole and trimetazidene - A. K. Zhanataev; I. A. Miroshkina; I. B. Tsorin; Z. V. Chayka; S. A. Kryzhanovskii; A. D. Durnev (LLC "Publisher OKI", 2018)
Resume. Relevance. Alcoholic cardiomyopathy (ACM) is a specific heart muscle disease found in individuals with a history of long-term heavy alcohol consumption. Their underlying mechanisms are poorly known, leading to a lack of effective therapy. Related with oxidative stress DNA damage and cell death play an essential role in the development of alcoholic cardiomyopathy. The aim of present study - using previously developed translation model to evaluate the levels of DNA damage and apoptosis in the myocardium of rats with ACM and modulating effect of cardioprotective drugs. Methods. ACM was established by forced alcoholization of rats (10 % ethanol solution as the only source of drinking water for 24 weeks; mean daily ethanol consumption was 5.0-6.5 g/kg). Trimetazidine (20 or 30 mg/kg), fabomotizole (15 mg/kg) or their combination (20 + 15 mg/kg) were injected ip, daily during following 4 weeks of abstinence. DNA damage was evaluated using alkaline and neutral comet assay. Apoptosis was assessed by TUNEL assay in paraffin-embedded sections. Results. No DNA damage or apoptosis of the myocardial cells was observed in rats with alcoholic cardiomyopathy at the abstinence period. A decrease in the level of cardiomyocytes with a high degree of DNA fragmentation, referred to as "hedgehog" DNA comets and that are presumably cells at the stage of autophagic fragmentation of chromatin, was revealed. Treatment of rats at the abstinence period with cardioprotective drugs trimetazidine and fabomotizole or their combination raised "hedgehog" DNA comets level up to control value. Conclusion. Our findings allows considering the appearance of cardiomyocytes with highly fragmented DNA as an important mechanism for regulating and maintaining myocardial homeostasis in ACM.